A narrow band BPF for UWB RFID reader circuit for frequency extraction - Hossain, A. K. M. Zakir; Ibrahimy, Muhammad Ibn; Motakabber, S. M. A. (IJEAIS, 2017)
In this article, a narrow band, open circuited planar microstrip band pass filter has been proposed. Existing RFID reader circuits has to generate a constant chirp signal to read the conventional microstrip resonator type tag. Use of the VCO is well established for this application. However, in case of large bandwidth (>4GHz) chirp generation it’s still challenging for the researchers. This problem can be mitigated by using as many numbers of mixer-filter combinations as needed. Successful implementation of this topology centres around the precise design of a very narrow (<2% fractional bandwidth) band BPF. The proposed structure has been designed, simulated and fabricated for 5.4 GHz. It is observed that the fractional bandwidth of the BPF is less than 2% of the center frequency. The simulation and measured S-Parameters are in good agreement. The final bandwidth of the designed filter is 100 MHz and the dimensions 24.3 mm X 5 mm.